Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 7 - Section 7.2 - Rational Exponents - Exercise Set - Page 522: 67



Work Step by Step

Use the rule $(a^m)^n= a^{mn}$ to obtain: $=y^{-\frac{2}{3} \cdot \frac{1}{4}} \\=y^{-\frac{2(1)}{3(4)}} \\=y^{-\frac{2}{12}} \\=y^{-\frac{1}{6}}$ Use the rule $a^{-m} = \dfrac{1}{a^m}$ to obtain: $=\dfrac{1}{y^{\frac{1}{6}}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.